Tari Kreasi Penyandar, Transformasi Tahapan Yang Dilalui Penari Sandar di Pura Dalem Padonan Desa Pererenan - I Putu Ananta Wira Adhyatma; Sulistyani; Ni Wayan Suartini (UPT Pusat Penerbitan LP2MPP Institut Seni Indonesia Denpasar, 2025)
AbstractThe dance piece titled Penyandar is a new creative work. This dance piece draws inspiration from the personalexperiences of the choreographer during her time as a Pregina Telek/Sandar at Pura Dalem Padonan in the village ofPererenan. This work transforms the stages undergone by the Pregina Telek/Sandar. Penyandar comes from the wordSandar, which is another term for Tari Telek, which then received the prefix “Pe-” referring to the performer of theTelek/Sandar dance itself. This dance has a religious theme and is performed in groups using seven male dancers. Themethod used is the Angripta Sesolahan creation method (creating dances), which involves planning, conceptualizing,designing, refining, and finalizing. The accompanying music for the Sandar dance uses the Musical Instrument DigitalInterface (MIDI) application as its medium, utilizing samples from the Semara Pegulingan Saih Pitu gamelan ensemble,which lasts 11 minutes.Keywords: Penyandar, religion, New creation.